Bank Profitability Analysis Before and After Covid 19 at PT Bank Sumut Syariah KCP Medan - Novariany Ka’u; Sugianto Sugianto (Penerbit Jurnal Indonesia, 2022)
This study aims to analyze bank profitability before and during the pandemic (COVID – 19) at the Sumatran Islamic Bank KCP Medan. Islamic banks in Indonesia face a number of challenges amid the Covid-19 outbreak.During the current Covid-19 pandemic, several Islamic banks have experienced disruptions in their profitability. For this reason, it is necessary to conduct research to analyze the impact of covid 19 on bank performance by analyzing the bank's profitability. This research is a qualitative research with a descriptive approach. From this research, it can be concluded that Islamic banks in Indonesia still depend on the income obtained from murabahah financing and tend not to develop mudharabah financing or musyarakah financing. In fact, if mudharabah and musyarakah financing can be managed properly by Islamic banks and channeled to mudharib-mudharib who are experts in their fields, this can increase the income earned by Islamic banks themselves. The data taken is 1 month.